HINDU SPIRITUAL GROUPS IN INDONESIA AND THEIR ACTIVE ROLES IN MAINTAINING HARMONY - Yoga Segara, I Nyoman (Analisa: Journal of Social Science and Religion, 2018)
Hinduism in Indonesia has been embraced in various ways. In addition to individual adoption, the conversion to Hinduism has also be performed through religious groups, which later develop by adjusting the local customs. The distinction between one adherent to another is essentially unified by the same theology. Panca Sraddha is one of the binders of Buddhis’ belief to Brahman, Atman, Karmaphala, Punarbhawa or Samsara, and Moksa. By utilizing this similarity, people who belong to Hinduism in Indonesia can live in harmony with other fellow Hindus as well as other religious communities, including Indonesian "indigenous religion" followers. Taking the fact into account; however, there are some Sampradaya or spiritual groups which aim to study the religion deeply by making the Vedic scriptures as the only source of the teachings which might lead them into certain challenging situations in terms of living in harmonious life. The problematic situations were addressed through this qualitative research, which employed interviews, observations, as well as document analysis as source of data. This study concludes that the three religious spiritual groups in Hinduism described in this article are now well-welcomed as an integral part of Indonesian Hindus and members of community in general, although they initially have been rejected at the beginning of their development. In keeping harmony among religious believers, these three spiritual groups, Hare Krishna, Sai Baba, and Brahma Kumaris are actively managing pleasant relations with the Indonesian government, Hindu councils, traditional Hindus, and other religious communities. They have performed strategies of dialogue, cooperation, and social service through humanitarian activities based on love and universal values.